A strong decline of the endangered Apollo butterfly over 20 years in the archipelago of southern Finland - Kukkonen Jonna M; Mussaari Maija; Fred Marianne S; Brommer Jon E (SPRINGER, 2022)
Insect groups are declining worldwide; Lepidoptera are among the taxa most affected in terrestrial ecosystems. The main drivers of these declines are a diverse set of factors relating to environmental change including habitat loss, pollution, and climate change. In 2019 and 2020, we surveyed 118 and 90 islands, respectively, in southern Finland's archipelago for occupancy of Parnassius apollo larvae and counted the abundance of their host plant Hylotelephium telephium. Compared with historical data (1997-2003), the occupancy of Apollo butterfly larvae has decreased remarkably from about 75% to about 20% of islands and abundance declined as well. However, the abundance of their host plant has not changed. Occupancy models showed that the present occupancy probability is not affected by host plant numbers, and shows substantial colonization-extinction dynamics making the population vulnerable to stochastic extinction.
Implications for insect conservation Our results show that this Apollo butterfly population is declining, and conservation actions are needed.